Sub-millisecond firing synchrony of closely neighboring pyramidal neurons in hippocampal CA1 of rats during delayed non-matching to sample task - Takahashi, Susumu; Sakurai, Yoshio (Frontiers in Neural Circuits, 2009)
Firing synchrony among neurons is thought to play functional roles in several brain regions. In theoretical analyses, firing synchrony among neurons within sub-millisecond precision is feasible to convey information. However, little is known about the occurrence and the functional significance of the sub-millisecond synchrony among closely neighboring neurons in the brain of behaving animals because of a technical issue: spikes simultaneously generated from closely neighboring neurons are overlapped in the extracellular space and are not easily separated. As described herein, using a unique spike sorting technique based on independent component analysis together with extracellular 12-channel multi-electrodes (dodecatrodes), we separated such overlapping spikes and investigated the firing synchrony among closely neighboring pyramidal neurons in the hippocampal CA1 of rats during a delayed non-matching to sample task. Results showed that closely neighboring pyramidal neurons in the hippocampal CA1 can co-fire with sub-millisecond precision. The synchrony generally co-occurred with the firing rate modulation in relation to both internal (retention and comparison) and external (stimulus input and motor output) events during the task. However, the synchrony occasionally occurred in relation to stimulus inputs even when rate modulation was clearly absent, suggesting that the synchrony is not simply accompanied with firing rate modulation and that the synchrony and the rate modulation might code similar information independently. We therefore conclude that the sub-millisecond firing synchrony in the hippocampus is an effective carrier for propagating information—as represented by the firing rate modulations—to downstream neurons.